2018
DOI: 10.1186/s12939-018-0744-x
|View full text |Cite
|
Sign up to set email alerts
|

Racial and cultural minority experiences and perceptions of health care provision in a mid-western region

Abstract: BackgroundDisparities across a number of health indicators between the general population and particular racial and cultural minority groups including African Americans, Native Americans and Latino/a Americans have been well documented. Some evidence suggests that particular groups may receive poorer standards of care due to biased beliefs or attitudes held by health professionals. Less research has been conducted in specifically non-urban areas with smaller minority populations.MethodsThis study explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 45 publications
(36 reference statements)
0
53
0
Order By: Relevance
“…In contrast, a small minority of FGDs participants stated that they had positive health care experiences while being in India. Some studies also report that migrants received good-quality health care whilst working abroad [ 20 , 32 ]. Possible reasons for this improvement include the lifestyle changes and health benefits that accompanied them which some migrant workers in the US experienced [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a small minority of FGDs participants stated that they had positive health care experiences while being in India. Some studies also report that migrants received good-quality health care whilst working abroad [ 20 , 32 ]. Possible reasons for this improvement include the lifestyle changes and health benefits that accompanied them which some migrant workers in the US experienced [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a small minority of FGDs participants stated that they had a positive health care experiences while being in India. Some studies also report that migrants received good-quality health care whilst working abroad [19,31]. Possible reasons for this improvement include the lifestyle changes and health bene ts that accompanied them which some migrant workers in the US experienced.…”
Section: Discussionmentioning
confidence: 99%
“…However, extant literature suggests that many AI/AN patients do not consider their relationships with healthcare providers to evince trust or mutual communication (Keltner, Kelly, & Smith, 2004). Relational issues described by AI/AN patients include patterns of ineffectual communication; perceived cultural insensitivity and discrimination by providers; and aggressive or dominating approaches to care delivery from non-AI/AN providers (Shepherd et al, 2018;Vasilevska, Ross, Gesink, & Fisman, 2012;Warne, Kaur, & Perdue, 2012). For example, Walls et al (2015) found that over a third of the surveyed 218 adult American Indian patients with type two diabetes mellitus reported experiencing microaggressions from healthcare providers.…”
Section: Ai/an Patient and Provider Rel Ations Hipsmentioning
confidence: 99%
“…In the Walls et al (2015) study, microaggressions elevated patients' stress and sense of distrust and resulted in worsening symptoms and increased hospitalizations over a 1-year period. Generally, AI/AN patients report higher incidences of poor treatment from providers, resulting in decreased satisfaction and increased reluctance to engage in biomedically based treatment (Shepherd et al, 2018).…”
Section: Ai/an Patient and Provider Rel Ations Hipsmentioning
confidence: 99%
See 1 more Smart Citation